2022
DOI: 10.3390/nu14040893
|View full text |Cite
|
Sign up to set email alerts
|

Paraxanthine Supplementation Increases Muscle Mass, Strength, and Endurance in Mice

Abstract: Paraxanthine is a natural dietary ingredient and the main metabolite of caffeine in humans. Compared to caffeine, paraxanthine exhibits lower toxicity, lesser anxiogenic properties, stronger locomotor activating effects, greater wake promoting properties, and stronger dopaminergic effects. The purpose of this study was to evaluate the potential beneficial effects of paraxanthine supplementation on muscle mass, strength, and endurance performance in comparison to the control and other ingredients commonly used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…A dose-response study confirmed the nootropic effects of paraxanthine in acute doses as little as 50 mg [ 24 ]. Moreover, Jäger and coworkers [ 65 ] reported that paraxanthine supplementation increased muscle mass, strength, and endurance in mice. While preclinical and mechanistic data suggest some advantages of paraxanthine over caffeine, no study has compared the nootropic effects of ingesting paraxanthine with or without caffeine on cognition after intense exercise.…”
Section: Discussionmentioning
confidence: 99%
“…A dose-response study confirmed the nootropic effects of paraxanthine in acute doses as little as 50 mg [ 24 ]. Moreover, Jäger and coworkers [ 65 ] reported that paraxanthine supplementation increased muscle mass, strength, and endurance in mice. While preclinical and mechanistic data suggest some advantages of paraxanthine over caffeine, no study has compared the nootropic effects of ingesting paraxanthine with or without caffeine on cognition after intense exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that further trials are needed to corroborate the causal path, caffeine and some of its metabolites, including the main one, paraxanthine, show notable potential pharmacological interests, sometimes different from caffeine, for example on nitric oxide (NO) neurotransmission [ 44 , 45 ]. Jäger and colleagues showed interesting results of paraxanthine supplementation on grip strength, muscle mass, treadmill performance and NO in mice, all with seemingly less toxicity compared to caffeine [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that further trials are needed to corroborate the causal path, caffeine and some of its metabolites, including the main one, paraxanthine, show notable potential pharmacological interests, sometimes different from caffeine, for example on nitric oxide (NO) neurotransmission [ 44 , 45 ]. Jäger and colleagues showed interesting results of paraxanthine supplementation on grip strength, muscle mass, treadmill performance and NO in mice, all with seemingly less toxicity compared to caffeine [ 45 , 46 ]. On the other hand, theophylline has already shown an effect of reducing susceptibility to fatigue by improving ventilatory functions through its bronchodilator effect and on the contractility of the diaphragm [ 47 ] and is commonly used in the elderly in the context of asthma or chronic airway diseases [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Paraxantine, the primary metabolite of caffeine, has similar pharmacological properties to caffeine but has been claimed to have reduce anxiogenic effects and reduced toxicity [39] compared with caffeine. It is unclear whether the therapeutic vs. deleterious effects of paraxanthine would differ from those of caffeine in the setting of headache disorders.…”
Section: Potential Alternatives To Caffeinementioning
confidence: 99%